Historical origins of sukuk as a popular instrument in modern Islamic finance - ERİŞ, İSMAİL (My University, 2021)
Since the 1980s, a very rapid development has been observed in financing methods called interest-free finance or Islamic finance. ukūk, also called interest-free or Islamic bonds, is undoubtedly one of the leading factors of this development. The main subject of this study is to find out the origins of ukūk in Islamic history. The first examples of ukūk as used in modern Islamic finance appeared in the markets in the late 1970s. For this reason, using the end of the 1970s as a turning point, our study sought an answer to the question of whether there were financial instruments similar to ukūk in the history of Islam before the 1970s, based on the similarities to the functioning of the ukūk types after the 1970s. In our study, although there are differences in various aspects in the history of Islam, it has been seen that there are instruments that are similar to the functioning of ukūk in the modern period in some other respects. Accordingly, it can be said that ukūk is an instrument that has its origins in Islamic history, but has been developed with a new understanding in the modern period.

1980’li yıllardan itibaren faizsiz finans veya İslami finans olarak adlandırılan finansman yöntemlerinde çok hızlı bir gelişme gözlenmiştir. Faizsiz veya İslami tahvil olarak da adlandırılan ukūk, şüphesiz bu gelişmenin önde gelen faktörlerinden biridir. Bu çalışmanın ana konusu, ukūkun İslam tarihindeki kökenlerini ortaya çıkarmaktır. Modern İslami finansta kullanılan ilk ukūk örnekleri, piyasalarda 1970’lerin sonlarında ortaya çıkmıştır. Bu nedenle 1970’lerin sonunu bir dönüm noktası olarak kullanan çalışmamız, 1970’lerden sonraki ukūku türlerinin işleyişine benzerliklerine dayalı olarak 1970’lerden önceki dönemde İslam tarihinde ukūk benzeri finansal enstrümanların var olup olmadığı sorusuna cevap aramıştır. Çalışmamızda İslam tarihinde her ne kadar çeşitli açılardan farklılıkları olsa da diğer bazı açılardan modern dönemdeki ukūkun işleyişi ile benzerliklerin olduğu görülen enstrümanların olduğu görülmüştür. Buna göre ukūkun kökenleri İslam tarihinde olan, ancak modern dönemde yeni bir anlayışla geliştirilmiş bir enstrüman olduğu söylenebilir
Modern İslami Finansta Popüler Bir Araç Olarak ukūkun Tarihsel Kökenleri
Keywords: şukūk; sak; esham; para vakıfları; icareteyn; bey’u’l-ine; bey’ bi’l-istiğlal; bey’ bi’l-vefa; akk; cash foundations; ijaratayn; bay’ al-‘inah; bay’ bi’listighlal; bay’ bi’l-wafā